Role of Kupffer cells in tolerance induction after liver transplantation - Zheng, Weixiong; Yang, Lingxiang; Jiang, Shiming; Chen, Mingxiang; Li, Jinzheng; Liu, Zuojing; Wu, Zhongjun; Gong, Jianping; Chen, Yong (Frontiers in Cell and Developmental Biology, 2023)
Currently, liver transplantation has reached a level of maturity where it is considered an effective treatment for end-stage liver disease and can significantly prolong the survival time of patients. However, acute and chronic rejection remain major obstacles to its efficacy. Although long-term use of immunosuppressants can prevent rejection, it is associated with serious side effects and significant economic burden for patients. Therefore, the investigation of induced immune tolerance holds crucial theoretical significance and socio-economic value. In fact, the establishment of immune tolerance in liver transplantation is intricately linked to the unique innate immune system of the liver. Kupffer cells, as a crucial component of this system, play a pivotal role in maintaining the delicate balance between inflammatory response and immune tolerance following liver transplantation. The important roles of different functions of Kupffer cells, such as phagocytosis, cell polarization, antigen presentation and cell membrane proteins, in the establishment of immune tolerance after transplantation is comprehensively summarized in this paper. Providing theoretical basis for further study and clinical application of Kupffer cells in liver transplantation.